OPTIMALISASI BERTINGKAT BERBASIS INTEGRITAS ELASTOMER PROGRESSIVE CAVITY PUMP (PCP) - Mohd Wirawan Putra Pamungkas; Hendra Budiman (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2026)
This research aims to optimize oil recovery through technical evaluation and redesign of the Progressing Cavity Pump (PCP) artificial lift system in wells AW-01 and AW-02 at PT. Pertamina EP Asset 1 Jambi Field. The method used is formation productivity analysis using the Vogel Inflow Performance Relationship (IPR) curve, volumetric efficiency evaluation, Total Dynamic Head (TDH) calculation, and stator elastomer integrity threshold testing based on fluid abrasiveness and rotation speed (RPM). The results of this research activity are the identification of different optimization needs for both wells; AW-01 is optimized by increasing the Variable Speed Drive (VSD) frequency to 47 Hz (277 RPM) to reach 62% Qmax, while AW-02 requires a redesign using a 20 H 500 pump type to achieve the 80% Qmax target (791.348 bfpd) at a safe speed of 150 RPM. The Conclusion, Significance, and implications of the Research show that the tiered optimization strategy successfully increased production by 3.87 bopd for AW-01 and 9.45 bopd for AW-02. This study demonstrates that maintaining elastomer integrity by limiting RPM is crucial for preventing mechanical failure. The implication is that this approach provides a new operational standard in extending pump run life while maximizing reservoir potential economically and sustainably.